Echocardiographic Strain Abnormalities Precede Left Ventricular Hypertrophy Development in Hypertrophic Cardiomyopathy Mutation Carriers - Canciello, Grazia; Lombardi, Raffaella; Borrelli, Felice; Ordine, Leopoldo; Chen, Suet-Nee; Santoro, Ciro; Frisso, Giulia; di Napoli, Salvatore; Polizzi, Roberto; Cristiano, Stefano; Esposito, Giovanni; Losi, Maria-Angela (International journal of molecular sciences, 2024)
Hypertrophic cardiomyopathy (HCM) is a genetic disease characterized by unexplained left ventricular hypertrophy (LVH), diastolic dysfunction, and increased sudden-death risk. Early detection of the phenotypic expression of the disease in genetic carriers without LVH (Gen+/Phen−) is crucial for emerging therapies. This clinical study aims to identify echocardiographic predictors of phenotypic development in Gen+/Phen−. Sixteen Gen+/Phen− (one subject with troponin T, six with myosin heavy chain-7, and nine with myosin-binding protein C3 mutations), represented the study population. At first and last visit we performed comprehensive 2D speckle-tracking strain echocardiography. During a follow-up of 8 ± 5 years, five carriers developed LVH (LVH+). At baseline, these patients were older than those who did not develop LVH (LVH−) (30 ± 8 vs. 15 ± 8 years, p = 0.005). LVH+ had reduced peak global strain rate during the isovolumic relaxation period (SRIVR) (0.28 ± 0.05 vs. 0.40 ± 0.11 1/s, p = 0.048) and lower global longitudinal strain (GLS) (−19.8 ± 0.4 vs. −22.3 ± 1.1%; p < 0.0001) than LVH- at baseline. SRIVR and GLS were not correlated with age (overall, p > 0.08). This is the first HCM study investigating subjects before they manifest clinically significant or relevant disease burden or symptomatology, comparing at baseline HCM Gen+/Phen− subjects who will develop LVH with those who will not. Furthermore, we identified highly sensitive, easily obtainable, age- and load-independent echocardiographic predictors of phenotype development in HCM gene carriers who may undergo early preventive treatment.